Medulloblastoma with Excessive Nodularity: Radiographic Features and Pathologic Correlate. (22nd October 2012) - Yeh-Nayre, L. A.; Malicki, D. M.; Vinocur, D. N.; Crawford, J. R.
Abstract : Medulloblastoma with extensive nodularity is a rare subtype of the most common malignant childhood brain tumor and has been associated with more favorable prognosis. The authors report the case of a 10-month-old girl with a posterior fossa tumor of excessive nodularity with decreased diffusivity on diffusion-weighted magnetic resonance imaging sequences and robust grape-like postgadolinium contrast enhancing features. The unique neuroradiographic features were confirmed by histopathology and a diagnosis of medulloblastoma with extensive nodularity was made. This case highlights the importance of recognizing this unique medulloblastoma subtype preoperatively, as the more favorable outcome may preclude less aggressive medical management.